The Mechanisms of Disease Caused by Acinetobacter baumannii - Morris, Faye C.; Dexter, Carina; Kostoulias, Xenia; Uddin, Muhammad Ikhtear; Peleg, Anton Y. (Frontiers in Microbiology, 2019)
Acinetobacter baumannii is a Gram negative opportunistic pathogen that has demonstrated a significant insurgence in the prevalence of infections over recent decades. With only a limited number of “traditional” virulence factors, the mechanisms underlying the success of this pathogen remain of great interest. Major advances have been made in the tools, reagents and models to study A. baumannii pathogenesis, and this has resulted in a substantial increase in knowledge. This article provides a comprehensive review of the bacterial virulence factors, the host immune responses and animal models applicable for the study of this important human pathogen. Collating the most recent evidence characterizing bacterial virulence factors, their cellular targets and genetic regulation, we have encompassed numerous aspects important to the success of this pathogen, including membrane proteins and cell surface adaptations promoting immune evasion, mechanisms for nutrient acquisition and community interactions. The role of innate and adaptive immune responses are reviewed and areas of paucity in our understanding are highlighted. Finally, with the vast expansion of available animal models over recent years, we have evaluated those suitable for use in the study of Acinetobacter disease, discussing their advantages and limitations.